2015
DOI: 10.1093/database/bav106
|View full text |Cite
|
Sign up to set email alerts
|

Differential ligand-signaling network of CCL19/CCL21-CCR7 system

Abstract: Chemokine (C-C motif) receptor 7 (CCR7), a class A subtype G-Protein Coupled Receptor (GPCR), is involved in the migration, activation and survival of multiple cell types including dendritic cells, T cells, eosinophils, B cells, endothelial cells and different cancer cells. Together, CCR7 signaling system has been implicated in diverse biological processes such as lymph node homeostasis, T cell activation, immune tolerance, inflammatory response and cancer metastasis. CCL19 and CCL21, the two well-characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…The pathways used by CCR7 to facilitate metastasis are not fully understood. It has been reported that CCR7 facilitates cancer progression by manipulating cancer cells' anoikis and mobility [82] as well as controlling the tumor microenvironment, including the inflammatory responses, immune tolerance and T cell activation [105,106]. Downstream potential signaling mediators of CCR7 have been reported to be associated with metastasis, such as ALDH3A2, AnXA6, EpCAM, and PVR [107].…”
Section: Molecular Aspects Of C-c Chemokine Receptor 7 (Ccr7) Signalimentioning
confidence: 99%
“…The pathways used by CCR7 to facilitate metastasis are not fully understood. It has been reported that CCR7 facilitates cancer progression by manipulating cancer cells' anoikis and mobility [82] as well as controlling the tumor microenvironment, including the inflammatory responses, immune tolerance and T cell activation [105,106]. Downstream potential signaling mediators of CCR7 have been reported to be associated with metastasis, such as ALDH3A2, AnXA6, EpCAM, and PVR [107].…”
Section: Molecular Aspects Of C-c Chemokine Receptor 7 (Ccr7) Signalimentioning
confidence: 99%
“…I CCL T consistent with reports from other laboratories that have shown CCL21 is better at inducing migration [40] and probably reflects the difference in the intracellular pathways activated by the two ligands. [41] In control experiments, the colon cell line DLD-1 and SW480 which express little CCR7, showed no increase in motility in the presence of CCL21 whilst CCR7 expressing prostate PC-3 cell line did (Figure 1D, 1E).…”
Section: Evaluation Of Ccr7 and Hif-mentioning
confidence: 90%
“…CCR7 and its ligands are crucial for DC migration [2325]. The receptor is rapidly upregulated in mature DCs to regulate their migration into the lymphatics via a CCL21 gradient and then to drain lymph nodes in response to CCL19/MIP-3 β [21].…”
Section: Discussionmentioning
confidence: 99%